Risk factors for electroconvulsive therapy-induced fever: a retrospective case-control study - Can-Jin Deng; Can-Jin Deng; Jian-Wen Yang; Jian-Wen Yang; Zi-Zhe Liu; Zi-Zhe Liu; Ting Ning; Ting Ning; Sha Nie; Sha Nie; Xiong Huang; Xiong Huang; et al. (Frontiers in Psychiatry)
BackgroundElectroconvulsive therapy (ECT)-induced fever can significantly affect patient experience, treatment adherence, and the course of treatment. However, little is known about the prevalence of ECT-induced fever and its associated risk factors in patients with major mental disorders (MMD).MethodsThis retrospective, case-control study included 113 cases and 226 age-matched controls (1:2). The case group comprised patients who exhibited an axillary temperature of ≥37.5°C (99.5°F) at least once within 24 hours post-ECT. Patients diagnosed with MMD underwent ECT between January 1, 2021, and December 31, 2021, at a large psychiatric hospital in China. Demographic and clinical data were extracted from the electronic chart management system (ECMS) for both groups.ResultsThe prevalence of ECT-induced fever in patients with MMD was 6.8% [113/1,674, 95% confidence interval (CI): 5.6% to 8.0%], with a session-based prevalence of 1.1% (130/11,570, 95% CI: 0.9% to 1.3%). Multivariate logistic regression analysis identified paliperidone [odds ratios (OR)=2.5, 95% CI: 1.2 to 4.9] as a risk factor, while quetiapine (OR=0.4, 95% CI: 0.3 to 0.8) was found to be protective. No significant association between etomidate and ECT-induced fever was observed in univariate analysis (p>0.05).ConclusionsThis study found a relatively low prevalence of ECT-induced fever. Paliperidone was identified as a risk factor, while quetiapine had a protective effect. Etomidate was not significantly associated with ECT-induced fever in patients with MMD.